Addictive Psychopathology, Smoking, and Drinking Among Adolescents in One Region - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study purported to investigate the psychopathology of addiction, smoking, and drinking among adolescents in one region. Addictive psychopathology was investigated in terms of anxiety, depression, impulsivity, and aggression. This study performed a secondary analysis of statistical data from a survey with 28,256 participants; a two-sample t-test was used. The results of this study showed that anxiety, depression, impulsivity, and aggression differed according to current smoking and drinking habits. Addictive psychopathology is related to smoking and drinking behavior; therefore, prevention of addictive psychopathology through smoking and drinking behavior correction is required.